(untitled) (Environment & Health, 2025)
The article reflects the current global trends in assessing the safety of packaging paper, polymer products, kitchen cutlery and crockery made of various materials, including plastics. The article also shows the peculiarities of implementation of EU Regulations 10/2011 and 1935/2004 and the differences in the use of Sanitary and Epidemiological Norms (in particular, Sanitary and Epidemiological Norms 42-123-4240-86), which until recently were in force in Ukraine in relation to these studies. The aim of the study. Analysis of the current state of the regulatory and methodological framework in force in the EU and Ukraine, and analysis of our own test results for the migration of toxic metals, VOCs (volatile organic compounds - formaldehyde, alcohols, ethyl acetate, acetaldehyde) from materials in contact with food and beverages. Materials and methods. The study used paper, polymer, glass, metal products and packaging materials used in the food industry. The content of toxic substances and metals was determined using photometry, gas chromatography, and inductively coupled plasma optical emission spectrometry. Conclusions. The research has shown that the implementation and use of European standards for migration studies requires the use of a wider range of model environments, validation of new safety assessment indicators and the introduction of modern, more sensitive analytical instruments.